2020
DOI: 10.1007/s11113-020-09606-7
|View full text |Cite
|
Sign up to set email alerts
|

Population Change and Income Inequality in Rural America

Abstract: This paper examines the effects of population growth and decline on county-level income inequality in the rural United States from 1980 to 2016. Findings from previous research have shown that population growth is positively associated with income inequality. However, these studies are largely motivated by theories of urbanization and growth in metropolitan areas, and do not explicitly test for differences between the impacts of population growth and decline. Examining the effects of both forms of population c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Alternatively, population decline could lead to excess housing stock resulting in decreased housing prices for those who remain in these places (Mulder 2006). The vast majority of counties that have experienced population decline in these studies are also classified as rural (Butler et al 2020; Johnson and Lichter 2019), which for this study may mean that population change may also be associated with larger relative changes in affordability in rural counties compared to urban counties.…”
Section: Conceptual Framework and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, population decline could lead to excess housing stock resulting in decreased housing prices for those who remain in these places (Mulder 2006). The vast majority of counties that have experienced population decline in these studies are also classified as rural (Butler et al 2020; Johnson and Lichter 2019), which for this study may mean that population change may also be associated with larger relative changes in affordability in rural counties compared to urban counties.…”
Section: Conceptual Framework and Backgroundmentioning
confidence: 99%
“…Population growth is also related to income inequality. Butler and colleagues (2020) found that high growth nonmetropolitan counties experienced a decline in income inequality relative to stable growth counties, while population decline counties became more unequal over time. Similar trends may cross over to inequality in affordability, where growing populations create more equitable housing markets and it is easier for households of all income groups to find suitable housing.…”
Section: Conceptual Framework and Backgroundmentioning
confidence: 99%
“…Lack of economic opportunities in rural areas is one of the primary drivers of outmigration (McLaughlin, Shoff, and Demi 2014;Petrin, Schafft, and Meece 2014). Depopulation, in turn, exacerbates income inequality (Butler et al 2020).…”
Section: Finding Well-paid Stable Employmentmentioning
confidence: 99%
“…Changes in income inequality across the United States have played out unevenly across space, with levels and changes in inequality varying considerably across localities (Butler et al 2020;Peters 2012;Thiede et al 2020;Van Heuvelen 2018). For example, the range of countylevel Gini Indexes exceeded 30 points between 1970 and 2000, from 23.7 to 57.9 (Moller et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has identified important socioeconomic and demographic determinants of local income inequality (Alderson and Nielsen 1999;Butler et al 2020;Moller et al 2009;Peters 2012;Van Heuvelen 2018), including ethno-racial composition, population size and structure, industrial structure, and educational attainment. Identifying the strength and direction of these correlates has allowed scholars to evaluate a number of important theories.…”
Section: Introductionmentioning
confidence: 99%